Understanding Learning Within a Commercial Video Game: A Case Study - Fowler, Allan (Auckland University of Technology, 2014)
There has been considerable interest and debate about the value of video games. There are researchers that suggest that video games are useful tools for engaging learners in engaging and authentic learning experiences (Gee, 2003; McGonigal, 2012; Shaffer, Squire, Halverson, & Gee, 2005; Squire, 2008; Steinkuehler, 2005). However, there are researchers that suggest that video games are harmful, addictive, or exploitive (Chan & Rabinowitz, 2006; Fisher, 1994; Spain & Vega, 2005; Phillips, Rolls, Rouse, & Griffiths, 1995) and disruptive to the learning experience (Kirriemuir & McFarlane, 2003). There has been considerable research on the educational value of educational video games, and the findings have found that the educational video games are very engaging and interesting. However, as the organisations that make the educational games lack the production budgets results in the video games not being widely adopted by the target consumer. Furthermore, many of these video games incorporate what Bruckman (1999) referred to as ‘chocolate covered broccoli’ approach. This is when a video game is presented as a reward for completing a learning outcome (Bruckman, 1999). Through a review of the literature, gaps in the literature on the educational value of commercial video games were identified. Therefore, this research sought to undertake an empirical study into what types of learning transpires while using a commercial video game. As the process of learning is typically an internal process, the task of identifying if and when learning transpired is sometimes challenging. Although traditional methods of assessments and verbal reflection provide some indicators that learning may have transpired, this research sought to obtain additional evidence through using observational methods. This additional method was possible through advances in video based eye tracking cameras. The availability of high-resolution desk mounted video based eye tracking camera made it possible for this research to obtain quantitative data on potential indicators of cognition or problem solving; endogenous eye blinks and fixations that lasted longer than 600 milliseconds (ms). Ponder & Kenned (1927) suggest that the endogenous (having an internal cause or origin) blink is an indicator of human cognition. This theory has been supported by more recent researchers (Stern, Walrath, & Goldstein, 1984; Orchard & Stern, 1991; Tanaka & Yamaoka, 1993). The other indicator or cognition is when the eye fixates on a specific object or stimuli. The duration the eyes are fixed on a particular object can potentially indicate the amount of processing that is taking place (Just & Carpenter, 1976; Just & Carpenter, 1980). This study used a desktop video-based eye tracking camera to monitor and record the endogenous eye blinks and eye fixations. While the studies into the value of educational video games have provided a valuable contribution to knowledge, very few investigated the transferability of the learning that took place within the game to an external context. To address this limitation, the study conducted in this paper measured pre and post exposure to the learning principles embedded in the treatment. Furthermore, this study observed any improvements in the embedded learning concepts through a physical exercise that replicated the in-game learning concepts to an out-of-game test. The research questions are: RQ 1: What learning takes place when playing the video game World of Goo? RQ 2: Does problem solving ability improve through playing video games? RQ 3: Do the participants that played the video game World of Goo learn tower construction from playing the game? This study identified that conceptual learning did transpire through exposure to a commercial video game. The adult participants exhibited this learning through in-game performance and how to play the game. The children exhibited this learning through demonstrating an advanced understanding of the embedded learning concepts within the game to the out-of-game tests. Furthermore, the children exhibited improvements in in-game performance and reductions in cognition and cognitive problem solving after they were exposed to additional treatment. These findings will be valuable to educators who find it challenging to educate twenty-first-century learners. These learners have grown up with Internet-connected multimedia devices and the pedagogical concepts embedded in traditional media (books, video) may not provide a complete learning experience that they are familiar with. Further, these findings will be valuable for video game developers as the method employed could be used by developers to help identify the parts of the game that the user is struggling with. These findings could also be used by developers or regulators in helping identify the most appropriate target age group for the game. These findings could also be used in future research as this research validated a method for collecting empirical data on individual cognition.
Keywords: Commercial video games; Learning